2008
DOI: 10.1186/1471-2164-9-401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mapping of quantitative trait loci associated with waterlogging tolerance in barley (Hordeum vulgare L.)

Abstract: Background: Resistance to soil waterlogging stress is an important plant breeding objective in high rainfall or poorly drained areas across many countries in the world. The present study was conducted to identify quantitative trait loci (QTLs) associated with waterlogging tolerance (e.g. leaf chlorosis, plant survival and biomass reduction) in barley and compare the QTLs identified across two seasons and in two different populations using a composite map constructed with SSRs, RFLP and Diversity Array Technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
143
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 36 publications
6
143
1
Order By: Relevance
“…Leaf chlorosis is a direct symptom of flooding that has been successfully applied in wheat (Boru et al 2001), soybean (Cornelious et al 2005) and barley (Li et al 2008). In our study, a MFVW that integrates a wilting index, a chlorosis score and the dead leaf proportion of waterlogged plants was deployed to measure WT.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf chlorosis is a direct symptom of flooding that has been successfully applied in wheat (Boru et al 2001), soybean (Cornelious et al 2005) and barley (Li et al 2008). In our study, a MFVW that integrates a wilting index, a chlorosis score and the dead leaf proportion of waterlogged plants was deployed to measure WT.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies germination rate and plant survival have been used as characteristics of waterlogging tolerance in barley (Li et al, 2008) and rice (Nandi et al, 1997), as they visibly respond to waterlogging. In the current study, plant parameters measured under anaerobic conditions relative to aerobic conditions were the other main parameters for investigating waterlogging tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, QTL-QY2 and also QTL-QY4 on 4H are located in similar positions to a QTL identified in TX9425 9 cv. Yerong by Li et al (2008) based on dry matter reduction after 3 weeks of waterlogging stress. QY is used as an indirect way of predicting the biomass growth reduction of waterlogged seedlings and the genes responsible may be the same.…”
Section: Discussionmentioning
confidence: 99%
“…With only seven chromosomes, barley has been widely used in different QTL analyses (Ahmed et al 2013;Close et al 2009) and also for WLT (Li et al 2013). Li et al (2008) identified several QTL linked to leaf chlorosis, plant survival and plant residual biomass, while Zhou et al (2012) found four QTLs linked to an index calculated from scores of leaf chlorosis and plant survival of waterlogged plants in outdoor tanks filled with soil. The latter method was used by Zhou (2011) to obtain more accurate phenotyping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation